2002
DOI: 10.2144/02334rr02
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Functional Proteomics: Mammalian Genome Annotation Using CD-Tagging

Abstract: A self-inactivating CD-tagging retroviral vector was used to introduce epitope and GFP tags into genes and proteins in NIH 3T3 cells. Several hundred cell clones, each expressing GFP fluorescence in a distinctive pattern, were isolated. Molecular analysis showed that a wide variety of genes and proteins, some known and some newly discovered, had been tagged. The analysis also revealed that, in the great majority of instances, the abundance and cellular location of the tagged protein mirrored that of its untagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…In addition to these datasets, a major National Cancer Institute-funded project led by Jonathan W. Jarvik, Peter B. Berget and Robert F. Murphy is beginning to provide images of the subcellular location of randomlytagged proteins in 3T3 cells. Preliminary wide-field 2D images (40×, pixel size 0.475 microns) have been acquired for approximately 100 clones produced by random CD-tagging [5][6][7]. By sequencing DNA adjacent to the tag, the tagged gene has been identified (if it is present in current sequence databases).…”
Section: Sources Of Data On Subcellular Locationmentioning
confidence: 99%
“…In addition to these datasets, a major National Cancer Institute-funded project led by Jonathan W. Jarvik, Peter B. Berget and Robert F. Murphy is beginning to provide images of the subcellular location of randomlytagged proteins in 3T3 cells. Preliminary wide-field 2D images (40×, pixel size 0.475 microns) have been acquired for approximately 100 clones produced by random CD-tagging [5][6][7]. By sequencing DNA adjacent to the tag, the tagged gene has been identified (if it is present in current sequence databases).…”
Section: Sources Of Data On Subcellular Locationmentioning
confidence: 99%
“…However, we have previously proposed that unsupervised methods are more appropriate to the analysis of protein subcellular location patterns [4]. We have used the retroviral CD-tagging technology developed by Jarvik, Berget and colleagues [12] to collect increasing numbers of images of mouse 3T3 cells expressing proteins randomly-tagged with GFP and then cluster them into Subcellular Location Trees [6,13,14]. As the number of tagged lines examined has increased, the number of statistically distinguishable clusters has also increased ( Table 1).…”
Section: Learning Subcellular Patterns Using Cluster Analysis: Subcelmentioning
confidence: 99%
“…Some large-scale projects have used fluorescence microscopy to screen hundreds to thousands or proteins for particular patterns or to assign proteins to major location classes. 11,13,20,22 A particular ambitious and valuable project has been the tagging of all predicted protein coding regions in the yeast Saccharomyces cerevisiae.…”
Section: Determination Of Protein Locationmentioning
confidence: 99%
“…Previous studies have shown that CD-tagging has minimal impact on protein folding, function and localization. 13 Here, we combine CD-tagging, automated microscopy and automated analysis to identify statistically distinguishable location patterns NIH 3T3 cells. We present the combination of high-throughput methods from tagging to analysis as well as fully automated methods of imaging and analysis.…”
Section: Cd-tagging Of Nih 3t3 Cellsmentioning
confidence: 99%
See 1 more Smart Citation